CYPA and CD147 expression analysis in human glioblastoma: Evidence for a correlation with reduced survival. Issue 1 (2019) - Matthews, V; Candy, PA; West, KA; Knuckey, NW; Robbins, P; Jeffcote, T
No abstract available